A carbon-silicon composite negative electrode material and its preparation method and application

By adding zinc source and tetraethyl silicate hydrolysis during the carbon pyrolysis process, a high-stability carbon-silicon composite anode material is formed, which solves the cycle stability and safety of the silicon anode material, and achieves a high degree of high Improved specific capacity and Coulomb efficiency.

CN115498172BActive Publication Date: 2024-12-13EVE POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211371341.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-03
Publication Date
2024-12-13
Estimated Expiration
2042-11-03
Patent Text Reader

Abstract

The present invention provides a carbon-silicon composite negative electrode material and a preparation method and application thereof. The preparation method comprises the following steps: (1) mixing a biomass raw material with an alkali solution, heating the mixture, filtering the mixture, and obtaining a carbon-containing filtrate; mixing the carbon-containing filtrate with a zinc source, heating and stirring the mixture, and calcining the mixture to obtain a calcined material; (2) mixing the calcined material with an acid solution, filtering and drying the mixture to obtain a flaky carbon material; (3) mixing the flaky carbon material, a surfactant, and a solvent, adding ammonia water and ethanol to obtain a solution A, mixing a silicon source with an organic solvent to obtain a solution B, mixing the solutions A and B, mixing the obtained solid with an inorganic salt and an active metal powder, grinding the solid, and calcining the solid to obtain the carbon-silicon composite negative electrode material; the zinc source causes the carbon to form a porous layered structure during the pyrolysis of the carbon, thereby providing more formation sites for the attachment of silicon oxide generated by the hydrolysis of tetraethyl silicate, which is conducive to the close combination of the two.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries and relates to a carbon-silicon composite negative electrode material and a preparation method and application thereof. Background Art

[0002] Silicon-based materials have a theoretical mass specific capacity of up to 4200 mAh g -1 It is far superior to graphite and is currently recognized as the next generation of negative electrode materials for lithium-ion batteries. However, due to some physical and chemical properties of silicon, the industrial application of silicon negative electrodes has progressed slowly. Unlike the intercalation mechanism of graphite, silicon crystals present a three-dimensional bulk structure of covalent tetrahedrons, and charge and discharge by forming Li-Si alloys with lithium. The volume expansion rate of Li-Si alloys is as high as 320%. Strong stress will cause silicon particles to break and fall off from the electrode sheet, causing a sharp drop in battery cycle stability and an increase in safety risks.

[0003] CN103022446A discloses a lithium-ion battery silicon oxide / carbon negative electrode material and a preparation method thereof, which adopts a porous silicon oxide preparation and carbon coating process, with a graphite material as a core, a porous silicon oxide as a middle layer, and an organic pyrolytic carbon as an outermost coating layer to prepare the negative electrode material.

[0004] CN103682359A discloses a negative electrode material, which at least includes silicon oxide and carbon material. It adopts simple liquid phase coating to add silicon oxide to a solvent in which a carbon material precursor is dissolved, and then sintering is performed after precipitation to obtain the negative electrode material.

[0005] Carbon materials and silicon materials are compounded by physical or chemical means, such as surface coating or mutual dispersion. On the one hand, this can effectively alleviate the breakage of silicon materials during the charging and discharging process; on the other hand, it can improve the conductivity of the composite material while avoiding the shedding of silicon.

[0006] However, although the modification of silicon-carbon negative electrode can improve the cycle performance of silicon to a certain extent, it has not brought into play the advantage of high specific capacity of silicon negative electrode. Therefore, it is necessary to further optimize the silicon-carbon negative electrode and develop negative electrode materials with high specific capacity and high coulombic efficiency. Summary of the invention

[0007] The purpose of the present invention is to provide a carbon-silicon composite negative electrode material and a preparation method and application thereof. In the present invention, a zinc source is added during carbon pyrolysis to obtain a porous layered carbon matrix, and the porous layered carbon matrix can provide more formation sites for silicon. The present invention uses tetraethyl silicate as a silicon source, and silicon oxide generated after hydrolysis of the silicon source adheres to the porous layered carbon matrix, and the two are tightly combined and have high stability.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a carbon-silicon composite negative electrode material, the preparation method comprising the following steps:

[0010] (1) mixing a biomass raw material with an alkali solution, heating the mixture, filtering the mixture, and obtaining a carbonaceous filtrate; mixing the carbonaceous filtrate with a zinc source; heating and stirring the mixture, and calcining the mixture in one step to obtain a calcined material;

[0011] (2) mixing the calcined material obtained in step (1) with an acid solution, filtering and drying to obtain a flaky carbon material;

[0012] (3) The flaky carbon material obtained in step (2), a surfactant and a solvent are mixed, and a mixed solution of ammonia water and ethanol is added, which is recorded as solution A. The silicon source is mixed with an organic solvent, which is recorded as solution B. Solution A is mixed with solution B, and after solid-liquid separation, the obtained solid is mixed with an inorganic salt and an active metal powder and ground, and the carbon-silicon composite negative electrode material is obtained through a two-step calcination treatment.

[0013] During the preparation of the carbon-silicon composite negative electrode material of the present invention, the zinc source causes the carbon to form a porous layered structure during carbon pyrolysis, thereby facilitating the subsequent attachment of silicon oxide generated by hydrolysis of tetraethyl silicate, providing more formation sites, and facilitating the close combination of the two.

[0014] Preferably, the biomass raw material in step (1) includes any one of corn straw, wheat straw or rice straw, or a combination of at least two of them.

[0015] Preferably, the alkali solution comprises potassium hydroxide solution and / or sodium hydroxide solution.

[0016] Preferably, the temperature of the heating treatment is 150-180°C, for example, 150°C, 155°C, 160°C, 170°C or 180°C.

[0017] Preferably, the heating treatment time is 8 to 12 hours, for example: 8 hours, 9 hours, 10 hours, 11 hours or 12 hours.

[0018] Preferably, the zinc source comprises zinc nitrate and / or zinc acetate.

[0019] Preferably, the mass ratio of the carbon material to the zinc source in the carbon-containing filtrate is 1:(0.5-1), for example: 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1, etc.

[0020] Preferably, the temperature of the heating and stirring in step (1) is 70-90°C, for example, 70°C, 75°C, 80°C, 85°C or 90°C.

[0021] Preferably, the heating and stirring time is 10 to 15 hours, for example, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours.

[0022] Preferably, the atmosphere of the one-step calcination comprises argon and / or nitrogen.

[0023] Preferably, the temperature of the one-step calcination is 700-750°C, for example, 700°C, 710°C, 720°C, 730°C, 740°C or 750°C.

[0024] Preferably, the one-step calcination time is 1 to 3 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours.

[0025] Preferably, the acid solution in step (2) comprises any one of hydrofluoric acid, nitric acid, sulfuric acid or hydrochloric acid, or a combination of at least two thereof.

[0026] Preferably, the suction filtration and drying comprises suction filtration with deionized water for 2 to 4 times, and then suction filtration with anhydrous ethanol for 1 to 2 times before drying.

[0027] Preferably, the drying temperature is 70-90°C, for example, 70°C, 75°C, 80°C, 85°C or 90°C.

[0028] Preferably, the drying time is 5 to 10 hours, for example, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours.

[0029] Preferably, in step (3), the mass ratio of the flaky carbon material to the surfactant is (3-6):1, for example: 3:1, 3.5:1, 4:1, 4.5:1 or 5:1, etc.

[0030] Preferably, the organic solvent comprises ethanol.

[0031] Preferably, the mixing of solution A and solution B in step (3) comprises injecting solution A into solution B and stirring at 500-800 rpm (for example: 500 rpm, 550 rpm, 600 rpm, 700 rpm or 800 rpm, etc.) for 2-4 h, for example: 2 h, 2.5 h, 3 h, 3.5 h or 4 h, etc.

[0032] Preferably, the solid-liquid separation is followed by washing and drying.

[0033] Preferably, the drying temperature is 70-90°C, for example, 70°C, 75°C, 80°C, 85°C or 90°C.

[0034] Preferably, the drying time is 10 to 15 hours, for example, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours.

[0035] Preferably, the inorganic salt in step (3) comprises NaCl.

[0036] Preferably, the active metal powder comprises magnesium powder.

[0037] Preferably, the mass ratio of the solid, the inorganic salt and the active metal powder is (1.2-2):(10-15):1, for example: 1.2:10:1, 1.2:12:1, 1.5:12:1, 1.8:12:1 or 2:15:1, etc.

[0038] Preferably, the atmosphere of the two-step calcination treatment includes hydrogen and argon.

[0039] Preferably, the temperature of the two-step calcination treatment is 600-800°C, for example, 600°C, 650°C, 700°C, 750°C or 800°C.

[0040] Preferably, the two-step calcination treatment is followed by acid washing, water washing and vacuum drying.

[0041] Preferably, the pickling detergent comprises hydrochloric acid.

[0042] Preferably, the vacuum drying temperature is 50-70°C, for example, 50°C, 55°C, 60°C, 65°C or 70°C.

[0043] Preferably, the vacuum drying time is 8 to 12 hours, for example, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours.

[0044] In a second aspect, the present invention provides a carbon-silicon composite negative electrode material, which is prepared by the method described in the first aspect, and the carbon-silicon composite negative electrode material includes a lamellar carbon matrix and silicon oxide loaded on the surface of the lamellar carbon carrier.

[0045] In the carbon-silicon composite negative electrode material of the present invention, the flaky carbon layer is beneficial to improving the overall electronic conductivity of the composite material on the one hand, and can effectively alleviate the shedding of active materials caused by volume expansion and contraction of Si during charging and discharging, while reducing the migration distance of lithium ions and improving ion conductivity. The above synergistic effect makes the flaky silicon-carbon composite negative electrode material prepared by the present invention have excellent cycle stability and rate performance.

[0046] In a third aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the carbon-silicon composite negative electrode material of the second aspect.

[0047] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode sheet as described in the third aspect.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] (1) In the present invention, a porous layered carbon matrix can be prepared by adding a zinc source during the carbon pyrolysis process. The porous layered carbon matrix can provide more formation sites for silicon. The present invention uses tetraethyl silicate as a silicon source. Silicon oxide generated after hydrolysis of the silicon source adheres to the porous layered carbon matrix. The two are tightly combined and have high stability.

[0050] (2) The lamellar silicon-carbon composite negative electrode material prepared by the present invention has excellent cycle stability (at a current density of 0.84 A / g, after 200 cycles, the capacity remains above 1468.4 mAh / g) and rate performance (at a current density of 8.4 A / g, the capacity can still be maintained above 574.9 mAh / g). DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0052] Example 1

[0053] This embodiment provides a carbon-silicon composite negative electrode material, and the preparation method of the carbon-silicon composite negative electrode material is as follows:

[0054] (1) 20 g of dried corn stalks were crushed and soaked in 40 mL of deionized water, filtered and dried in an oven at 80°C for 10 h, 4 g of dried corn stalk powder was put into a water heating tank, and 36 g of deionized water and 3 g of KOH were added, and heated in an oven at 160°C for 10 h; naturally cooled and filtered, 20 mL of the filtrate was taken, 1.5 g of zinc nitrate (i.e., the mass ratio of carbon material to zinc source was 1:0.75) was added, and the mixture was placed in an oil bath at 80°C and dried for 12 h while being stirred, and the dried material was transferred to a nickel crucible, placed in a tubular furnace under an Ar atmosphere, heated to 730°C at a heating rate of 5°C / min, and kept warm for 2 h, and cooled to obtain a calcined material;

[0055] (2) 10 mL HF and 20 mL deionized water were placed in a polytetrafluoroethylene beaker, and the above-mentioned calcined material was added. After stirring for 1 h, the mixture was filtered 3 times with deionized water, and then filtered once with anhydrous ethanol, and then dried in a forced air drying oven at 80 ° C for 8 h to obtain a flaky carbon material.

[0056] (3) 0.2 g of the carbon obtained in step 3 and 0.05 g of a surfactant were dispersed in 100 mL of deionized water, and a mixed solution of 26 mL of ethanol and 14.4 mL of ammonia water was added, marked as A. At room temperature, a mixed solution of 72.8 mL of ethanol and 7.2 mL of tetraethyl silicate (TEOS) was prepared, marked as B. After stirring evenly, solution A was injected into solution B, and stirred at 600 rpm for 3 h to obtain SiO2 uniformly attached to the above-mentioned lamellar carbon layer. The mixture was then separated and washed with water, and dried at 80°C for 12 h to obtain a solid powder. 0.8 g of the solid powder was taken and ground together with 6 g of NaCl and 0.5 g of magnesium powder in an agate mortar and mixed evenly. The mixture was then transferred to a 20 mL stainless steel crucible and placed in a tubular furnace. A 5% H2 / Ar mixed gas was introduced at 5°C min -1 The temperature is raised to 700° C. at a rate of 1000° C. to react, the product is pickled with dilute hydrochloric acid, then washed with water, and dried in a vacuum drying oven at 60° C. for 10 hours to obtain the carbon-silicon composite negative electrode material.

[0057] Example 2

[0058] This embodiment provides a carbon-silicon composite negative electrode material, and the preparation method of the carbon-silicon composite negative electrode material is as follows:

[0059] (1) 20 g of dried corn stalks were crushed and soaked in 40 mL of deionized water, filtered and dried in an oven at 80°C for 10 h, 4 g of dried corn stalk powder was put into a water heating tank, and 36 g of deionized water and 3 g of KOH were added, and heated in an oven at 160°C for 10 h; naturally cooled and filtered, 20 mL of the filtrate was taken, 1.8 g of zinc acetate (i.e., the mass ratio of carbon material to zinc source was 1:0.9) was added, and the mixture was placed in an oil bath at 85°C and dried for 11 h while stirring, and the dried material was transferred to a nickel crucible, placed in a tubular furnace under an Ar atmosphere, heated to 720°C at a heating rate of 5°C / min, and kept warm for 2 h, and cooled to obtain a calcined material;

[0060] (2) 10 mL of nitric acid and 20 mL of deionized water were placed in a polytetrafluoroethylene beaker, and the above-mentioned calcined material was added. After stirring for 1 h, the material was filtered with deionized water for 3 times, and then filtered with anhydrous ethanol for 1 time, and then placed in a forced air drying oven at 80° C. for 8 h to obtain a flaky carbon material;

[0061] (3) 0.25 g of the carbon obtained in step 3 and 0.05 g of a surfactant were dispersed in 100 mL of deionized water, and a mixed solution of 26 mL of ethanol and 14.4 mL of ammonia water was added, marked as A. At room temperature, a mixed solution of 72.5 mL of ethanol and 7.5 mL of tetraethyl silicate (TEOS) was prepared, marked as B. After stirring evenly, liquid A was injected into liquid B, and stirred at 600 rpm for 3 h to obtain SiO2 uniformly attached to the above-mentioned lamellar carbon layer. The mixture was then separated and washed with water, and dried at 80°C for 12 h to obtain a solid powder. 1 g of the solid powder was taken and ground together with 6 g of NaCl and 0.5 g of magnesium powder in an agate mortar and mixed evenly. The mixture was then transferred to a 20 mL stainless steel crucible and placed in a tubular furnace. A 5% H2 / Ar mixed gas was introduced at 5°C min -1 The temperature was raised to 710° C. at a rate of 1000 ℃ for reaction, the product was pickled with dilute hydrochloric acid, then washed with water, and dried in a vacuum drying oven at 60° C. for 10 h to obtain the carbon-silicon composite negative electrode material.

[0062] Example 3

[0063] The only difference between this embodiment and embodiment 1 is that the mass ratio of the carbon material to the zinc source in step (1) is 1:0.3 (ie, 0.6 g of zinc nitrate is added), and the other conditions and parameters are exactly the same as those in embodiment 1.

[0064] Example 4

[0065] The only difference between this embodiment and embodiment 1 is that the mass ratio of the carbon material to the zinc source in step (1) is 1:1.2 (ie, 2.4 g of zinc nitrate is added), and the other conditions and parameters are exactly the same as those in embodiment 1.

[0066] Comparative Example 1

[0067] The only difference between this comparative example and Example 1 is that no zinc source is added, and other conditions and parameters are exactly the same as those in Example 1.

[0068] Comparative Example 2

[0069] The only difference between this comparative example and Example 1 is that KOH is replaced by K2CO3, and the other conditions and parameters are exactly the same as those in Example 1.

[0070] Comparative Example 3

[0071] The only difference between this comparative example and Example 1 is that no NaCl is added during the grinding process in step (3), and the other conditions and parameters are exactly the same as those in Example 1.

[0072] Performance Test:

[0073] The silicon-carbon composite negative electrode materials prepared in Examples 1-4 and Comparative Examples 1-3 were prepared as negative electrodes of batteries, wherein the positive electrode counter electrode of the lithium half-battery was a metal lithium disc, the battery model was 2032, and the battery was tested for cycle performance and rate performance, and the test results are shown in Table 1.

[0074] The test conditions for the cycle performance and rate performance are to charge and discharge at a current of 0.84A / g in a voltage range of 3.0 to 0.01V at room temperature; the maximum current for the rate performance test is 8.4A / g. The test results are shown in Table 1:

[0075] Table 1

[0076] Capacity after 200 cycles (mAh / g) Capacity at current 8.4A / g (mAh / g) Example 1 1534.2 601.5 Example 2 1468.4 574.9 Example 3 1346.8 537.5 Example 4 1202.2 509.6 Comparative Example 1 954.8 489.9 Comparative Example 2 895.7 436.6 Comparative Example 3 736.8 389.9

[0077] As can be seen from Table 1, from Examples 1-2, the lamellar silicon-carbon composite negative electrode material prepared by the present invention has excellent cycle stability (at a current density of 0.84 A / g, after 200 cycles, the capacity remains above 1468.4 mAh / g) and rate performance (at a current density of 8.4 A / g, the capacity can still be maintained above 574.9 mAh / g).

[0078] By comparing Example 1 with Examples 3-4, it can be seen that in the preparation process of the carbon-silicon composite negative electrode material of the present invention, the mass ratio of the carbon material to the zinc source in the carbon filtrate in step (1) will affect the performance of the negative electrode material obtained. The mass ratio of the carbon material to the zinc source in the carbon filtrate is controlled at 1:0.5-1, and the performance of the negative electrode material obtained is better. If the amount of zinc source added is too large, the structure of the prepared carbon material collapses. If the amount of zinc source added is too small, the prepared carbon material sheet is thick and the carbon porosity is low.

[0079] By comparing Example 1 and Comparative Example 1, it can be seen that in the preparation process of the carbon-silicon composite negative electrode material of the present invention, the zinc source causes the carbon to form a porous layered structure during the carbon pyrolysis process, thereby facilitating the subsequent adhesion of silicon oxide generated by the hydrolysis of tetraethyl silicate, providing more formation sites, and facilitating the close combination of the two.

[0080] By comparing Example 1 and Comparative Example 2, it can be seen that in the preparation process of the carbon-silicon composite negative electrode material of the present invention, the selection of the type of alkali solution is very important. Sodium hydroxide and / or potassium hydroxide can form pores during carbon pyrolysis, but other alkali solutions (such as potassium carbonate) cannot play a pore-forming role, which leads to a significant decrease in the performance of the material.

[0081] By comparing Example 1 and Comparative Example 3, it can be seen that if no inorganic salt is added during the grinding process of step (3) of the present invention, there is no heat absorber during the magnesium heating process, the internal temperature of the material is too high to form excessive silicon carbide and the material is prone to agglomeration, which affects the performance of the material.

[0082] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a carbon-silicon composite negative electrode material, characterized in that: The preparation method comprises the following steps: (1) mixing a biomass raw material with an alkali solution, heating the mixture, filtering the mixture, and obtaining a carbonaceous filtrate; mixing the carbonaceous filtrate with a zinc source; heating and stirring the mixture, and calcining the mixture in one step to obtain a calcined material; (2) mixing the calcined material obtained in step (1) with an acid solution, filtering and drying to obtain a flaky carbon material; (3) The flaky carbon material obtained in step (2), a surfactant and a solvent are mixed, and a mixed solution of ammonia water and ethanol is added, which is recorded as solution A. Tetraethyl silicate is mixed with an organic solvent, which is recorded as solution B. Solution A is mixed with solution B, and after solid-liquid separation, the obtained solid is mixed with an inorganic salt and an active metal powder and ground, and the carbon-silicon composite negative electrode material is obtained through a two-step calcination treatment.

2. The preparation method according to claim 1, characterized in that The biomass raw material in step (1) includes any one of corn straw, wheat straw or rice straw, or a combination of at least two of them.

3. The preparation method according to claim 1, characterized in that: The alkali solution includes potassium hydroxide solution and / or sodium hydroxide solution.

4. The preparation method according to claim 1, characterized in that: The temperature of the heating treatment is 150-180°C.

5. The preparation method according to claim 1, characterized in that: The heating treatment time is 8 to 12 hours.

6. The preparation method according to claim 1, characterized in that: The zinc source includes zinc nitrate and / or zinc acetate.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the carbon material to the zinc source in the carbon-containing filtrate is 1:(0.5-1).

8. The preparation method according to claim 1, characterized in that: The temperature of the heating and stirring in step (1) is 70-90°C.

9. The preparation method according to claim 1, characterized in that: The heating and stirring time is 10 to 15 hours.

10. The preparation method according to claim 1, characterized in that: The one-step calcination atmosphere includes argon and / or nitrogen.

11. The preparation method according to claim 1, characterized in that: The temperature of the one-step calcination is 700-750°C.

12. The preparation method according to claim 1, characterized in that: The one-step calcination time is 1 to 3 hours.

13. The preparation method according to claim 1, characterized in that: The acid solution in step (2) includes any one of hydrofluoric acid, nitric acid, sulfuric acid or hydrochloric acid, or a combination of at least two of them.

14. The preparation method according to claim 1, characterized in that: The suction filtration and drying comprises suction filtration with deionized water for 2 to 4 times, and then suction filtration with anhydrous ethanol for 1 to 2 times before drying.

15. The preparation method according to claim 14, characterized in that: The drying temperature is 70-90°C.

16. The preparation method according to claim 14, characterized in that: The drying time is 5 to 10 hours.

17. The preparation method according to claim 1, characterized in that: The mass ratio of the flaky carbon material to the surfactant in step (3) is (3-6):

1.

18. The preparation method according to claim 1, characterized in that: The organic solvent includes ethanol.

19. The preparation method according to claim 1, characterized in that: The step (3) of mixing solution A with solution B comprises injecting solution A into solution B and stirring at 500 to 800 rpm for 2 to 4 hours.

20. The preparation method according to claim 1, characterized in that: After the solid-liquid separation, the product is washed with water and dried.

21. The preparation method according to claim 20, characterized in that: The drying temperature is 70-90°C.

22. The preparation method according to claim 20, characterized in that: The drying time is 10 to 15 hours.

23. The preparation method according to claim 1, characterized in that: The inorganic salt in step (3) includes NaCl.

24. The preparation method according to claim 1, characterized in that: The active metal powder includes magnesium powder.

25. The preparation method according to claim 1, characterized in that: The mass ratio of the solid, the inorganic salt and the active metal powder is (1.2-2):(10-15):

1.

26. The preparation method according to claim 1, characterized in that: The atmosphere of the two-step calcination treatment includes hydrogen and argon.

27. The preparation method according to claim 1, characterized in that: The temperature of the two-step calcination treatment is 600-800°C.

28. The preparation method according to claim 1, characterized in that: The two-step calcination treatment is followed by acid washing, water washing and vacuum drying.

29. The preparation method according to claim 28, characterized in that: The pickling detergent includes hydrochloric acid.

30. The preparation method according to claim 28, characterized in that The vacuum drying temperature is 50-70°C.

31. The preparation method according to claim 28, characterized in that: The vacuum drying time is 8 to 12 hours.

32. A carbon-silicon composite negative electrode material, characterized in that: The carbon-silicon composite negative electrode material is prepared by the method as described in any one of claims 1 to 31, and the carbon-silicon composite negative electrode material includes a lamellar carbon matrix and silicon oxide supported on the surface of the lamellar carbon carrier.

33. A negative electrode plate, characterized in that: The negative electrode plate comprises the carbon-silicon composite negative electrode material as claimed in claim 32.

34. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet as claimed in claim 33.